Endometriotic Follicular Fluid Affects Granulosa Cells’ Morphology and Increases Duplication Rate and Connexin-43 Expression - Loris Marin; Chiara Sabbadin; Giovanni Faggin; Claudia Maria Radu; Decio Armanini; Michele Paccagnella; Cristiano Salata; Luciana Bordin; Eugenio Ragazzi; Guido Ambrosini; Alessandra Andrisani (Biomolecules)
Endometriosis is a complicated condition characterized by inflammation, low oocyte quality, and decreased uterus receptivity, associated with fertility issues. This study aims to better understand the reduced pregnancy outcome in endometriosis by analyzing both the granulosa cells (GCs) and the follicular fluids (FFs) obtained during the assisted reproductive technology (ART)-related oocyte pick-up. Seventy patients, approaching our ART Center with the diagnosis of infertility for Age-Idiopathic Factor (AIF) (n = 36), endometriosis (ENDO) (n = 23), or male factor (MF) (n = 11), were enrolled in this study. GCs from each group were separately analyzed for morphology, replication, and expression of Connexin-43 and Follicle-Stimulating Hormone Receptor (FSHR) by microscopy, flow cytometry, and immunocytochemistry. Results show that FF in a culture medium allowed GCs to survive and replicate. Upon culturing GCs from each group with ENDO follicular fluid, increases were observed in both population doublings and in the development of fibroblast-like and muscle-like morphologies. Despite undergoing morphological changes, GCs consistently expressed FSHR. However, exposure to ENDO follicular fluid led to an upregulation of Connexin-43 expression across all GC groups. These findings suggest that in endometriosis, FF contains unidentified factors that can induce aberrant replication, morphological differentiation, and overexpression of Connexin-43, potentially contributing to follicular dysfunction.